2022
DOI: 10.1007/s11684-022-0930-5
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of influenza viruses in Shandong, Northern China during the COVID-19 pandemic

Abstract: Nonpharmaceutical interventions (NPIs) have been commonly deployed to prevent and control the spread of the coronavirus disease 2019 (COVID-19), resulting in a worldwide decline in influenza prevalence. However, the influenza risk in China warrants cautious assessment. We conducted a cross-sectional, seroepidemiological study in Shandong Province, Northern China in mid-2021. Hemagglutination inhibition was performed to test antibodies against four influenza vaccine strains. A combination of descriptive and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Throughout the COVID-19 pandemic, nonpharmaceutical interventions (NPIs), such as mandatory face coverings and social distancing, played a crucial role in reducing SARS-CoV-2 transmission rates. Studies have shown that COVID-19 NPIs were associated with reduced transmission of other viruses, such as HAdV and influenza (35)(36)(37). Our results support those findings; HAdV-F was not detectable in wastewater during July 2020-October 2021, when mandatory NPIs were in place in Ireland.…”
Section: Discussionsupporting
confidence: 89%
“…Throughout the COVID-19 pandemic, nonpharmaceutical interventions (NPIs), such as mandatory face coverings and social distancing, played a crucial role in reducing SARS-CoV-2 transmission rates. Studies have shown that COVID-19 NPIs were associated with reduced transmission of other viruses, such as HAdV and influenza (35)(36)(37). Our results support those findings; HAdV-F was not detectable in wastewater during July 2020-October 2021, when mandatory NPIs were in place in Ireland.…”
Section: Discussionsupporting
confidence: 89%
“…Although annual influenza vaccination is recommended to the population older than 65 yo, with high vaccine coverage (≥ 60% since 2017/18), the lowest seroprevalence of protective antibodies against influenza A viruses was observed for the older age groups (45–64 and 65+ yo). These results add to existing evidence of immune senescence and pre‐existing immunity and a faster decrease of antibody titers with time and age, more pronounced in the elderly [20, 23]. For influenza B, which only predominated in circulation during one season, 2014/2015, and co‐circulated with A(H3N2) during 2015/2016 and 2017/2018, we observed an increasing trend in the seroprevalence of protective antibodies with age.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that influenza vaccination provides effective and consistent antibody levels, and this difference is maintained at least until the subsequent summer. Other studies already showed the clear advantage of vaccine uptake in increasing antibody levels [ 20 ]. The data suggest that vaccination against influenza improves seroprevalence and protective antibody titers, contributing to a clearer understanding of the annual recommendations for influenza vaccine uptake, especially for the higher risk groups for severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A cross-sectional study in Shandong Province, Northern China found an extremely low (2.6%) overall vaccination rate. 28 The phenomenon of an annually decreasing influenza vaccination rate has also been observed in Guangzhou. Among children aged 6-59 months, influenza vaccination rates in the 2010-2012 season were 18.65% and 30.32% for cases and controls, respectively.…”
Section: Discussionmentioning
confidence: 94%